Lactosmart: A Novel Therapeutic Molecule for Antimicrobial Defense - Singh, Jiya; Vijayan, Viswanathan; Ahmedi, Saiema; Pant, Pradeep; Manzoor, Nikhat; Singh, Tej P.; Sharma, Pradeep; Sharma, Sujata (Frontiers in Microbiology, 2021)
The problem of antibiotic resistance has prompted researchers around the globe to search for new antimicrobial agents. Antimicrobial proteins and peptides naturally secreted by almost all the living organisms to fight infections and can be safer alternatives to chemical antibiotics. Lactoferrin (LF) is a known antimicrobial protein present in all body secretions. In this study, LF was digested by trypsin and the resulting hydrolysates were studied with respect to their antimicrobial properties. Among the hydrolysates, a 21 kDa basic fragment of lactoferrin (termed as Lactosmart) showed promise as a new potent antimicrobial agent. The antimicrobial studies were performed on various microorganisms including Shigella flexineri, Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli as well as fungal pathogens like Candida albicans, Candida tropicalis, and Candida glabrata. In addition, the lipopolysaccharide (LPS) binding properties of lactosmart were also studied using surface plasmon resonance technique in vitro, along with docking of LPS and molecular dynamics simulation studies. The results showed that lactosmart had better inhibitory effects against pathogenic microorganisms as compared to LF. The results of docking and MD simulation studies further validated the tighter binding of LPS to lactosmart as compared to LF. The two LPS binding sites have been characterized structurally in detail. Through these studies it has been demonstrated that in native LF, only one LPS binding site remains exposed due to its location being on the surface of the molecule. However, due to generation of lactosmart molecule, the second LPS binding gets exposed too. Since LPS is an essential and conserved part of the bacterial cell wall, the proinflammatory response in the human body caused by LPS can be targeted using the newly identified lactosmart. These findings highlight the immense potential of lactosmart in comparison of native lactoferrin in the antimicrobial defense. We propose that lactosmart can be further developed as antibacterial, antifungal and antibiofilm agent.